Effective software test automation : - Li, Kanglin (SYBEX, 2004)
Effective Software Test Automation goes well beyond the building of your own testing tool: it also provides expert guidance on deploying it in ways that let you reap the greatest benefits: earlier detection of coding errors, a smoother, swifter development process, and final software that is as bug-free as possible. Written for programmers, testers, designers, and managers, it will improve the way your team works and the quality of its products.